An investigation of a new cutaneous leishmaniasis endemic area in Western Sri Lanka. (16th September 2021) - Mallawarachchi, Chandana H; Chandrasena, Nilmini; Wijerathna, Tharaka; Dalpadado, Rasika; Mallawarachchi, Maleesha S M N S; Gunarathna, Dinesh G A M; Gunathilaka, Nayana
Abstract: Background: The aim was to investigate an emerging focus of cutaneous leishmaniasis (CL) in Gampaha district, Western Sri Lanka. Methods: Sociodemographics of CL patients in Mirigama, Gampaha district, were compared with controls using a structured questionnaire. Clinical data and geographic positioning system coordinates of patients were recorded. Sandflies collections were performed in four selected sites using indoor hand collection (162 units) and cattle-baited net traps (n=3). Results: Of 73 patients (mean age 43.6 y; SD 20), 58.9% were males. Lesions consisted of nodules (52.1%) and ulcers (47.9%). Single lesions were seen in 69.9% of patients, while 30.1% had multiple lesions. Except for one mucosal lesion, all the others were cutaneous. Treatment consisted of sodium stibogluconate and cryotherapy (46.6%), sodium stibogluconate (45.2%) or cryotherapy (8.2%). Multiple lesions were more likely to receive combination therapy (p=0.013). The majority of those employed (81.1%; 27/33) were engaged in outdoor work. Male gender, low education attainment and poor disease awareness were significant risk factors for CL (p<0.05). Four households reported multiple cases. Phlebotomus argentipes was detected in all cattle-baited net traps and 35.3% of indoor hand collection units. Conclusions: CL is emerging in Gamapha district with Mirigama as the epicentre. Case distribution indicates local transmission, with P. argentipes as the probable vector.